Coincidence of superficial brachiomedian artery and bitendinous palmaris longus: a case report - Kachlik, David; Hajek, Petr; Konarik, Marek; Krchov, Matej; Baca, Vaclav (Surgical and radiologic anatomy, 2016)
We present a unique unilateral case of a superficial brachiomedian artery that coincides with a variable palmaris longus muscle in a male cadaver. The superficial brachiomedian artery branched at the distal part of the right arm and coursed superficially in the cubital and antebrachial regions. Then it passed through the carpal canal and formed a complete superficial palmar arch by joining the trunk of the ulnar artery. The variable bitendinous palmaris longus was composed of a central belly and two asymmetrical tendons inserting mainly on the ulnar side of the flexor retinaculum. The knowledge of this arterial variant is of high clinical relevance for the catheterization, for the harvesting of the forearm artery as a graft, for the collateral circulation in cases of arterial occlusion, for surgical management of the carpal tunnel syndrome, or in cases of injury of the superficially located variant artery.
Keywords: Humans; kosterní svaly; arterie; Superficial brachiomedian artery; Muscle, Skeletal; předloktí; Median artery; Bitendinous palmaris longus; senioři; mužské pohlaví; Aged; Male; Arteries; lidé; Anatomic Variation; Forearm; anatomická variace